Analysis of rice (Oryza sativa l.) bioeconomy: Data Envelopment Analysis method highlights the need for cooperation to improve productivity and sustainability - Castro-Alvarez, Marcelo David (2026)
Rice (Oryza sativa L.) production is a cornerstone of Ecuador's economy. This research evaluates the efficiency of 609 production units during 2019, addressing the need for statistical robustness in agricultural efficiency estimators. Using a national representative survey, Data Envelopment Analysis (DEA) was applied under Variable Returns Scale (VRS) and Constant Returns to Scale (CRS). To account for sampling noise, the Simar & Wilson (2007) bootstrap procedure (2,000 replications) was implemented to provide bias-corrected scores and 95% confidence intervals. The bootstrap-corrected analysis revealed a mean technical efficiency of 0.632 (95% CI: 0.596 – 0.668), suggesting a potential 36.8% input reduction without output loss. Significant provincial heterogeneity was observed: Manabí led in technical efficiency (0.743), while El Oro achieved the highest cost efficiency (0.435) due to superior allocative performance. Conversely, Loja showed high technical proficiency (0.645) but the lowest allocative efficiency (0.197). Findings underscore that "one-size-fits-all" policies are inadequate; instead, province-specific interventions, focusing on scale optimization and financial training, are required to enhance the sustainability of Ecuador's rice bioeconomy.